1965
DOI: 10.1149/1.2423498
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Kinetics of Hydrogen and Oxygen Reactions on a Platinum Electrode in Acid Solution Using Pulse and Decay Techniques

Abstract: The influence of hydrogen partial pressure, current density, and temperature on the anodic oxidation of sorbed H and the anodic generation of sorbed O were determined. Electrode processes were evaluated and separated to give the following quantities: (a) the amount of H associated with a Pt surface and its immediate vicinity, (b) the extent of reaction of H atoms, absorbed in the metal interior, that migrate to the surface of the metal and are either ionized or react with O atoms, (c) the extent of reaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

1965
1965
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 10 publications
4
47
0
Order By: Relevance
“…2b) in acidic solution suggests formation of hydride or "dermasorbed" hydrogen (38,39) in a few atomic layers, just below the surface, and this causes the short, almost fiat, potential arrest in the decay curves, an effect not observed at active bright Pt electrodes in alkaline solution. In the case of Pd, due to the appreciable amount of H absorbed (normally >> H adsorbed), it takes a much longer time (>30s) than for Pt (ca.…”
Section: Resultsmentioning
confidence: 99%
“…2b) in acidic solution suggests formation of hydride or "dermasorbed" hydrogen (38,39) in a few atomic layers, just below the surface, and this causes the short, almost fiat, potential arrest in the decay curves, an effect not observed at active bright Pt electrodes in alkaline solution. In the case of Pd, due to the appreciable amount of H absorbed (normally >> H adsorbed), it takes a much longer time (>30s) than for Pt (ca.…”
Section: Resultsmentioning
confidence: 99%
“…However, the implicit assumption of a simple stoichiometry on the surface, that is, the assumption that one oxygen or hydrogen atom is adsorbed per metal atom at saturation, may be questioned. Furthermore it has recently been shown 101 that substantial amounts of hydrogen and even oxygen may be absorbed in platinum, so that care must be exercised in using hydrogen and oxygen charging methods for surface-area determination.…”
Section: Determination Of Equilibrium Adsorptionmentioning
confidence: 99%
“…This threepronged peak may be interpreted in terms of the desorption of adsorbed hydrogen from two and possibly three kinds of adsorption sites known (14)(15)(16) to exist on the Pt surface. The large background AT may be accounted for by the desorption of dermasorbed (25) and dissolved hydrogen (26,27) in the bulk metal. From x-ray diffraction studies of HNO3 passivated Pt-O alloy samples (1), it was found that the Pt lattice had been expanded suggesting that the dissolved oxygen had entered the Pt lattice.…”
Section: Discussionmentioning
confidence: 99%